Problem-Based Questions in the Development of Theoretical Thinking - ISHCHENKO, TATYANA N.; STEPANENKO, TATYANA A.; AKIMOVA, MARIA O. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Problem-based questions (PBQs) are mastered in the process of learning the subject matter and developing the ability to think. Constructing PBQs enabled students to develop their ability to consciously handle notions, formulate statements, make conclusions, and reveal contradictions. The ability to operate a system of notions while posing questions and looking for answers to them encourages meaningful communication.The findings were used to develop and implement an advanced training course for university teachers. The booster of theoretical thinking helps to switch from declarative knowledge given by a teacher to its joint discovery with learners. RESUMEN Las preguntas basadas en problemas (PBQ) se dominan en el proceso de aprender el tema y desarrollar la capacidad de pensar. La construcción de PBQ permitió a los estudiantes desarrollar su capacidad para manejar conscientemente nociones, formular declaraciones, sacar conclusiones y revelar contradicciones. La capacidad de operar un sistema de nociones mientras se plantean preguntas y se buscan respuestas fomenta la comunicación significativa. Los resultados se utilizaron para desarrollar e implementar un curso de formación avanzada para profesores universitarios. El refuerzo del pensamiento teórico ayuda a pasar del conocimiento declarativo proporcionado por un profesor a su descubrimiento conjunto con los alumnos.